Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 36690 by prof Abdo imad last updated on 04/Jun/18

let  f(t) =∫_0 ^1   ln(1 −tx^3 )dx  with 0<t≤1  find a simple form of f(t)   2)calculate ∫_0 ^1  ln(2−x^3 )dx .

letf(t)=01ln(1tx3)dxwith0<t1 findasimpleformoff(t) 2)calculate01ln(2x3)dx.

Commented bymaxmathsup by imad last updated on 03/Aug/18

we have f^′ (t) =−∫_0 ^1     (x^3 /(1−tx^3 ))dx =−∫_0 ^1 x^3 (Σ_(n=0) ^∞  t^n  x^(3n) dx  =−Σ_(n=0) ^∞  t^n  ∫_0 ^1  x^(3(n+1)) dx =−Σ_(n=0) ^∞   (t^n /(3n+4))  =−(1/((^3 (√t))^4 ))Σ_(n=0) ^∞     (((^3 (√t))^(3n  +4) )/(3n+4))  =−(1/((^3 (√t))^4 )) ϕ(^3 (√t)) with   ϕ(x) =Σ_(n=0) ^∞    (x^(3n+4) /(3n+4)) ⇒ϕ^′ (x)= Σ_(n=0) ^∞  x^(3n+3) =x^3  Σ_(n=0) ^∞  (x^3 )^n   =x^3  (1/(1−x^3 )) =(x^3 /(1−x^3 )) ⇒ϕ(x) = ∫_0 ^x   (t^3 /(1−t^3 )) dt +c  withc=ϕ(0)=0 ⇒  ϕ(x)=−∫_0 ^x  (t^3 /(t^3 −1))dt   =−∫_0 ^x    ((t^3 −1 +1)/(t^3 −1))dt =−x −∫_0 ^x   (dt/(t^3  −1)) let decompose  F(t) = (1/(t^3 −1))  F(t)= (1/((t−1)(t^2  +t+1))) =(a/(t−1)) +((bt+c)/(t^2  +t +1))  a =lim_(t→1) (t−1)F(t) =(1/3)  lim_(t→+∞) tF(t) =0 =a +b ⇒b =−a ⇒  F(t) = (1/(3(t−1))) −(1/3) ((t −3c)/(t^2  +t+1))  F(0) =−1 =−(1/3) +c ⇒c=(1/3)−1 =−(2/3) ⇒F(t)=(1/(3(t−1))) −(1/3) ((t +2)/(t^2  +t+1)) ⇒  ∫ F(t)dt = (1/3)ln∣t−1∣ −(1/6) ∫ ((2t +1+3)/(t^2  +t +1))dt  =(1/3)ln∣t−1∣ −(1/6)ln∣t^2  +t+1∣ −(1/2) ∫   (dt/((t+(1/2))^2  +(3/4))) but  ∫   (dt/((t+(1/2))^2  +(3/4))) =_(t+(1/2)=((√3)/2)u)     ∫      (1/((3/4)(1+u^2 ))) ((√3)/2) du=(4/3) ((√3)/2)  arctan(((2t+1)/(√3)))  =((2(√3))/3) arctan(((2t+1)/(√3))) ⇒  ϕ(x)=−x  − [ (1/3)ln∣t−1∣−(1/6)ln(t^2  +t+1)−((√3)/3) arctan(((2t+1)/(√3)))]_0 ^x   =−x −{(1/3)ln∣x−1∣−(1/6)ln(x^2  +x+1)−((√3)/3) arctan(((2x+1)/(√3)))+((√3)/3) arctan((1/(√3)))}  we have f^′ (t)=−(1/((^3 (√t))^4 )) ϕ(^3 (√t))   so the value of f^′ (x) is known..  be continued...

wehavef(t)=01x31tx3dx=01x3(n=0tnx3ndx =n=0tn01x3(n+1)dx=n=0tn3n+4 =1(3t)4n=0(3t)3n+43n+4=1(3t)4φ(3t)with φ(x)=n=0x3n+43n+4φ(x)=n=0x3n+3=x3n=0(x3)n =x311x3=x31x3φ(x)=0xt31t3dt+cwithc=φ(0)=0 φ(x)=0xt3t31dt=0xt31+1t31dt=x0xdtt31letdecompose F(t)=1t31 F(t)=1(t1)(t2+t+1)=at1+bt+ct2+t+1 a=limt1(t1)F(t)=13 limt+tF(t)=0=a+bb=a F(t)=13(t1)13t3ct2+t+1 F(0)=1=13+cc=131=23F(t)=13(t1)13t+2t2+t+1 F(t)dt=13lnt1162t+1+3t2+t+1dt =13lnt116lnt2+t+112dt(t+12)2+34but dt(t+12)2+34=t+12=32u134(1+u2)32du=4332arctan(2t+13) =233arctan(2t+13) φ(x)=x[13lnt116ln(t2+t+1)33arctan(2t+13)]0x =x{13lnx116ln(x2+x+1)33arctan(2x+13)+33arctan(13)} wehavef(t)=1(3t)4φ(3t)sothevalueoff(x)isknown.. becontinued...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com